Do Corporate Social Responsibility and International Financial Reporting Standards Implementation Matter? - Arshad Javed; Muhammad Aksar; Ayaz-ul Haq; Muhammad Naeem; Mujibah A. Sufyani (Universitas Pasundan, 2023)
This investigation examines how Pakistani banks listed on stock markets fare when International Financial Reporting Standards (IFRS) are implemented and Corporate Social Responsibility (CSR) activities are carried out. This study compares the financial performance of banks over a 3-year period before and following the introduction of IFRS, using a sample of all 22 banks listed on the Pakistan Stock Exchange. To address endogeneity and unobserved heterogeneity problems, the Generalized Method of Moments (GMM) is adopted. This study reveals that the implementation of IFRS has a favorable and considerable effect on the performance of the banks. CSR has a substantial impact on ROE but has a relatively smaller effect on ROA. We discovered that the performance indicators, such as BV and EPS, have little bearing on stock return of firms in the banking sectors. The MV of stock has dropped with the increasing standard of financial reporting, but the effect of COVID-19 cannot be ignored. The study reveals that IFRS implementation affects bank performance, while CSR significantly impacts ROE. IFRS adherence enhances performance, while CSR initiatives benefit stakeholders and contribute to social welfare and sustainable development.